2017
DOI: 10.1001/jama.2017.16190
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Single Dose of Oral Opioid and Nonopioid Analgesics on Acute Extremity Pain in the Emergency Department

Abstract: clinicaltrials.gov Identifier: NCT02455518.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
188
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 231 publications
(196 citation statements)
references
References 27 publications
5
188
0
3
Order By: Relevance
“…Nonsteroidal anti-inflammatory drugs, rather than opioids are first-line treatment for ankle sprains 38,39 and are just as effective as opioids in pain reduction. 10 We confirmed that the majority of subsequent prescriptions were unlikely to be related to the initial ankle sprain or chronic ankle pain. This suggests that association between larger prescriptions and increased likelihood of prolonged use could be due to other factors such as patients requesting opioids as default pain control, or the development of dependence or misuse.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Nonsteroidal anti-inflammatory drugs, rather than opioids are first-line treatment for ankle sprains 38,39 and are just as effective as opioids in pain reduction. 10 We confirmed that the majority of subsequent prescriptions were unlikely to be related to the initial ankle sprain or chronic ankle pain. This suggests that association between larger prescriptions and increased likelihood of prolonged use could be due to other factors such as patients requesting opioids as default pain control, or the development of dependence or misuse.…”
Section: Discussionsupporting
confidence: 70%
“…This is concerning because ankle sprains are a minor, self-limited condition for which there is likely to be little clinical benefit from opioids. 10 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analgesic model for children given ibuprofen after tonsillectomy has been described with a maximum effect ( E MAX ) of 6.5 pain units (Visual analogue scale 0‐10), an effect site concentration ( C e50 ) of 3.95 mg/L and a Hill coefficient of 1.45 . If we assume a reasonable analgesic target effect (TE) of a pain reduction by four pain units then a target concentration (TC) can be calculated:TC=Ce50xTEEMAX-TE=6.30.333333emmg/L…”
Section: Methodsmentioning
confidence: 99%
“…This was a blinded, randomised-controlled trial comparing single doses of four different oral analgesic preparations (non-opioid and opioid) for the treatment of acute extremity pain in the ED 4. The study was conducted in the USA at two large urban academic EDs.…”
Section: Methodsmentioning
confidence: 99%